C-Met Overexpression in Cervical Cancer, a Prognostic Factor and a Potential Molecular Therapeutic Target. (December 2017) - Refaat, Tamer; Donnelly, Eric D.; Sachdev, Sean; Parimi, Vamsi; El Achy, Samar; Dalal, Prarthana; Farouk, Mohamed; Berg, Natasha; Helenowski, Irene; Gross, Jeffrey P.; Lurain, John; Strauss, Jonathan B.; et al.
Abstract : Purpose: This study aimed to assess the association between pretreatment c-Met overexpression in local-regional advanced cervical cancer patients treated definitively with concurrent chemoradiation therapy (CRT) and treatment outcomes including overall survival (OS), progression-free survival (PFS), distant metastases (DM) control, and local-regional control (LC). Patients and Methods: This Institutional Review Board–approved study included cervical cancer patients treated definitively and consecutively with CRT. Evaluation of cytoplasmic immunoreactivity for c-Met was performed and scored semiquantitatively by 3 pathologists, blinded to the treatment outcomes, and incorporated both the intensity and percentage of immunoreactivity in invasive carcinoma ( H score). Treatment outcomes were reviewed and reported. Outcomes were stratified by c-Met overexpression and tumor characteristics. OS, PFS, LC, and DC rates were obtained via the Kaplan-Meier method and differences between groups were evaluated by the log-rank test. Hazard ratios were obtained via Cox regression for both univariate and multivariate analyses. Results: The 5-year OS, PFS, LC, and DC were 57.18%, 48.07%, 72.11%, and 62.85%, respectively. Ten (35.7%) and 18 patients (64.3%) had c-Met H index >30 and<30, respectively. c-Met overexpression was significantly associated with worse 3- and 5-year OS ( P =0.003), PFS ( P =0.002), LC ( P =0.01), and DC ( P =0.0003). Patients with c-Met overexpression had a hazard ratio of 6.297, 5.782, 6.28, and 18.173 for the risks of death, disease progression, local recurrence, and DM, respectively. Conclusion: c-Met overexpression could be a potential predictive marker and therapeutic target for local-regional advanced cervical cancer patients treated definitively with CRT.